A Department of Motor Vehicle–Based Intervention to Promote Organ Donor Registrations in New York State. (September 2017) - Feeley, Thomas Hugh; Anker, Ashley E.; Evans, Melanie; Reynolds-Tylus, Tobias
Context: Examination of efficacy of motor vehicle representative educational training and dissemination of promotional materials as a means to promote organ donation enrollments in New York State. Objective: To increase the number of New York State residents who consent to donation through the department of motor vehicle transactions during project period. Setting: County-run motor vehicle offices across New York State. Participants: Customers who present to New York Department of Motor Vehicle offices and the representative who work at designated bureaus. Interventions: point-of-decision materials including promotional posters, brochures, website, and the motor vehicle representative training sessions. Main Outcome Measures: Reasons for enrollment decision, knowledge/experience with donation, monthly consent rates, enrollment in state organ, and tissue registry. Results: Customers who elected not to register reported no reason or uncertainty surrounding enrollment. The representatives reported experience with donation, discussion with customers, and need for additional education on organ donation. Enrollment cards were mailed to 799 project staff; counties where offices participated in intervention did not indicate significantly higher monthly enrollments when comparing pre- to postenrollment rates. Conclusions: Use of point-of-decision materials and enrollment cards proved inexpensive method to register customers with a 3.6% return rate. Customers report low (27%) enrollment rate and reticence to consent to donation. Educational training sessions with representatives did not yield significant enrollment increases when evaluating data at county-level enrollment.